THE ROLE OF ARTIFICIAL INTELLIGENCE AND MACHINE LEARNING IN FINANCIAL FORECASTING AND DECISION-MAKING - Ooi Kok Loang; Wang Danqing; Li Chenxi; WangYizhu; Ren Xinyue; Hu Nana (International Journal of Accounting, Finance and Business, 2023)
This research explores the role of artificial intelligence (AI) and machine learning (ML) in financial forecasting and decision-making within A private Chinese Healthcare company. The study emphasises the importance of adequate preparation for implementing a new costing method, particularly the activity-based costing (ABC) approach. While traditional costing methods may be quicker, they often fail to account for significant variations in overhead costs. Although more time-consuming and meticulous, ABC provides well-categorised costing allocation sheets that facilitate easy understanding and decision-making. However, it is worth noting that ABC may not align seamlessly with generally accepted accounting principles (GAAP), potentially leading to conflicts among employees and management. This research highlights the need for A private Chinese Healthcare company's financial staff to be well-prepared to handle the transition to ABC, considering its potential impact on the organisation's cost management practices and internal dynamics. By embracing AI and ML tools, financial professionals can enhance their forecasting accuracy and make informed decisions, ensuring the efficient allocation of resources within the hospital setting.